HUBUNGAN POLA ASUH ORANG TUA DENGAN KEMAMPUAN SOSIALISASI ANAK RETARDASI MENTAL DI SEKOLAH LUAR BIASA(SLB) YAYASAN PEMBINAAN ANAK CACAT KELURAHAN MALALAYANG II KOTA MANADO - Tabaru, Gevin (Journal Of Community & Emergency, 2024)
Children with mental retardation experience obstacles in the field of education and in their communication. So that children will have obstacles in carrying out daily activities because of circumstances and intelligence that are below average which are not the same as normal children in general. So that the development of communication can be hampered in carrying out skills and independence for himself. They really need special education and proper parenting from both parents to improve their communication skills in carrying out daily activities at school, at home and in the surrounding community. The aim of the study is to find out the relationship between Parenting Patterns and Mental Retardation Socialization Ability in Special Schools (SLB) Foundation for the Development of Children with Disabilities, Manado. This research is an observational quantitative type of research using a cross- sectional study that is descriptive analytic in October 2022 and the sampling technique is the total population of the research site at the Manado Disabled Children’s Special School Foundation. The statistical test used is the "Chi-square" statistical test with a 95% confidence degree if . The results obtained that the P value = 0.009 while the value of = 0.05 so that the P value = 0.008 < = 0.05. Thus Ho is rejected and H1 is accepted, then there is a significant relationship between Parenting Patterns and Mental Retardation Socialization Ability in Special Schools (SLB) Foundation for the Development of Children with Disabilities, Manado. Conclusion From the results of the study The results of the research on parenting patterns in Special Schools (SLB) Foundation for the Development of Children with Disabilities, Malalayang II Village, Manado City are more democratic than authoritarian. The results of the research on the socialization ability of retarded children in the Special School (SLB) Foundation for the Development of Children with Disabilities, Malalayang II Village, Manado City were more normal than abnormal. There is a significant relationship between parenting styles and the socialization ability of retarded children at the Special School (SLB) Foundation for the Development of Disabled Children, Malalayang II Village, Manado City. Suggestions in this study are that this research can provide knowledge and understanding, as well as skills or information to the public about Parenting Parenting with Mental Retardation Socialization Ability in Special Schools.